Investigations into the static and dynamic fracture initiation and propagation toughness of AA2014-T6 incorporating temperatures effects. (28th March 2023) - Pandouria, Anoop Kumar; Tiwari, Vikrant
Graphical abstract: Highlights: Effect of temperature on initiation & propagation toughness of AA2014-T6 under static & dynamic loading conditions was studied. Modified Hopkinson pressure bar coupled with ultra-high speed imaging system was used for dynamic loading. 3D-DIC is found to be accurate and robust tool for the measurements of crack initiation time. Both static and dynamic fracture propagation toughness gradually increases with increasing temperature. The temperature has different effects on the static and dynamic fracture initiation toughness. Abstract: The fracture toughness of a material is an important parameter to quantify the reliability and safety of an engineering structure. In this article, the effect of loading rate and temperature on static and dynamic initiation and propagation toughness fracture behavior of AA2014-T6 is studied. Pre-crack three-point bend specimens are used in determining the static and dynamic fracture initiation and propagation toughness. Static three-point bend experiments are performed using a conventional UTM combined with the heating chamber at different displacement rates (1 mm/min, 10 mm/min, and 100 mm/min) and a wide temperature ranging from −150 °C to 200 °C. Similarly, the dynamic experiments are carried out on modified Hopkinson pressure bar (MHPB) under different loading rate and temperature. ASTM E399 was utilized in evaluating the static fracture initiation toughness, while the dynamic fracture initiation toughness is measured with the help of load point displacement (LPD) and crack initiation time. The 3D digital image correlation (DIC) in combination with ultra-high-speed imaging is used to calculate the crack initiation time and crack mouth opening displacement (CMOD). The energy conservation-based method was utilized in calculating the propagation fracture toughness in both static and dynamic loading conditions. Results show that the propagation toughness increases with temperature while the static fracture initiation toughness declines linearly. In addition, both initiation and propagation fracture toughness increases with the loading rates. Also the dynamic fracture investigation reveals that the positive rate sensitivity for dynamic propagation toughness increases with the increase in temperature. Results also show that the value of dynamic fracture initiation toughness is maximum at room temperature as the yield strength and plastic zone size are optimum in room temperature environments.